(3fcJ GdgejGf aj fcJ GdYejGfs - (3Ndjd Hf CjHc Hf YHO Gddg GdUaOj , UdGM GdOjf,J (B764 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi dGJOQcg GdCHUGQ hgh jOQc GdCHUGQ hHYO aEfi deG hbaJ Ydi cJGH GdeYGQa dGHf JjejI s
(3BNQgG (B:s
(3JQLeI jhfS Hf ejSQI hGNQg bhdg (B: (3hQhi dg CHh OGhO hGdJQePi hGHf eGLg BNQ GdcJGH s
(3HgG fXGe GdJYbjjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B315 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B114 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B352s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdCOHs